Adding value in barley malt rootlets as a source of 5'-phosphodiesterase : biochemical and thermodynamic evaluation of enzyme activity - Beluhan, Sunčica (Array, 2020)
A thermostable 5’-phosphodiesterase (5’-PDE, EC 3.1.4.1) was extracted from barley (Hordeum distichum var. Rex) malt rootlets. The purification procedure comprised acetone precipitation, S-Sepharose cation-exchange and DEAE-Sepharose anion-exchange chromatography. The enzyme was purified 101-fold with a recovery of 22% and a specific activity of 81.9 U mg-1 protein, Optimum enzyme activity was obtained at 70 °C, and pH 8.9. The SDS-PAGE profiling of the purified protein exhibited molecular weight of 116 kDa and revealed three sub-unit fractions of 26, 43, and 56 kDa making up its active configuration. The kinetic constants Km and Vmax were determined as 0.25 mM and 0.816 mmol min-1, respectively. Thermodynamic studies showed that the thermal inactivation of purified barley malt rootlets 5’-PDE followed the first-order kinetics, indicating inactivation energy (Ed) of 134 kJ mol-1. The half-life (t1/2) at 70 °C was estimated as 169 min. Thermodynamic parameters ΔH*, ΔS* and ΔG* were determined as a function of temperature and were 131.15 kJ mol-1, 37.01 kJ mol-1 K-1 and 118.4 kJ mol-1, respectively. The purified enzyme has long half-life with 11 days at 0 °C, 37 hours at 4 °C and 11 hours at room temperature. These results provide useful information about the factors that affects the activity of barley malt rootlets 5’-PDE and suggests a good indication for application of this enzyme in pharmaceutical and food industry.